2006
DOI: 10.1194/jlr.m600247-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in intramuscular lipid droplets and translocation of HSL in response to muscle contraction and epinephrine

Abstract: A better understanding of skeletal muscle lipid metabolism is needed to identify the molecular mechanisms relating intramuscular triglyceride (IMTG) to muscle metabolism and insulin sensitivity. An increasing number of proteins have been reported to be associated with intracellular triglyceride (TG), among them the PAT family members: perilipin, ADRP (for adipocyte differentiation-related protein), and TIP47 (for tail-interacting protein of 47 kDa). Hormone-sensitive lipase (HSL) is thought to be the major enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
101
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(110 citation statements)
references
References 43 publications
7
101
2
Order By: Relevance
“…The adipophilin staining identified these structures as lipid droplets. This punctate lipid droplet staining pattern is similar to that reported for TIP47 and adipophilin in rat soleus muscle (37). OXPAT-A ectopic expression drives increased rates of TAG accumulation and LCFA oxidation.…”
Section: Resultssupporting
confidence: 63%
“…The adipophilin staining identified these structures as lipid droplets. This punctate lipid droplet staining pattern is similar to that reported for TIP47 and adipophilin in rat soleus muscle (37). OXPAT-A ectopic expression drives increased rates of TAG accumulation and LCFA oxidation.…”
Section: Resultssupporting
confidence: 63%
“…So far, most of the published experimental work on exercise-induced lipolysis was focused on the role of HSL in this process. A number of studies demonstrate that this enzyme is involved in the mobilization of FAs in muscle and adipose tissue during exercise (14)(15)(16)(17). Moreover, in a very recent study, HSL was shown to be important for normal mobilization of FAs during exercise ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other lipid dropletassociated proteins from the PAT (perilipin/adipocyte differentiationrelated protein (ADRP)/tail-interacting protein of 47 kDa (TIP-47)) family are expressed in skeletal muscle and include ADRP and TIP-47. 15 Immunoinhibition studies indicate that HSL accounts for approximately 60% of total TG lipase activity in skeletal muscle at rest and almost all activity during contractions and adrenergic stimulation. 14,16,17 Adrenaline is a key activator of HSL and lipolysis.…”
Section: Intramuscular Lipolysismentioning
confidence: 99%
“…12 Morphological analysis of single muscle fibres reveals that HSL translocates to lipid droplets within myocytes in response to adrenaline and contraction and that ADRP and TIP-47 are localized to lipid droplets. 15 Association of HSL with ADRP may be essential for lipolytic control in skeletal muscle given the absence of perilipin A in this tissue. The role of PAT proteins in skeletal muscle requires further investigation.…”
Section: Intramuscular Lipolysismentioning
confidence: 99%